Ligand-gated ion channel interacting proteins and their role in neuroprotection - Li, Shupeng; Wong, Albert H. C.; Liu, Fang (Frontiers in Cellular Neuroscience, 2014)
Ion channel receptors are a vital component of nervous system signalling, allowing rapid and direct conversion of a chemical neurotransmitter message to an electrical current. In recent decades, it has become apparent that ionotropic receptors are regulated by protein-protein interactions with other ion channels, G-protein coupled receptors and intracellular proteins. These other proteins can also be modulated by these interactions with ion channel receptors. This bidirectional functional cross-talk is important for critical cellular functions such as excitotoxicity in pathological and disease states like stroke, and for the basic dynamics of activity-dependent synaptic plasticity. Protein interactions with ion channel receptors can therefore increase the computational capacity of neuronal signalling cascades and also represent a novel target for therapeutic intervention in neuropsychiatric disease. This review will highlight some examples of ion channel receptor interactions and their potential clinical utility for neuroprotection.